2000
DOI: 10.1523/jneurosci.20-10-03705.2000
|View full text |Cite
|
Sign up to set email alerts
|

Wild-Type Huntingtin Protects from Apoptosis Upstream of Caspase-3

Abstract: Expansion of a polyglutamine sequence in the N terminus of huntingtin is the gain-of-function event that causes Huntington's disease. This mutation affects primarily the medium-size spiny neurons of the striatum. Huntingtin is expressed in many neuronal and non-neuronal cell types, implying a more general function for the wild-type protein. Here we report that wild-type huntingtin acts by protecting CNS cells from a variety of apoptotic stimuli, including serum withdrawal, death receptors, and pro-apoptotic Bc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
231
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 351 publications
(247 citation statements)
references
References 42 publications
13
231
0
2
Order By: Relevance
“…We also identified several genes implicated in apoptosis, such as the Huntington disease gene Huntingtin, the double-strand DNA break repair gene hRAD54 (expressed higher in anaplastic tumors than in FH tumors), gamma-interferon-inducible gene IFI16 and caspase-10 (expressed lower in anaplastic tumors than in FH tumors). Wild-type Huntingtin has been shown to be antiapoptotic by inhibiting the conversion of procaspase-9 into active caspase-9 (Rigamonti et al, 2000). Huntingtin also regulates the transcription of BDNF (Zuccato et al, 2001).…”
Section: An Expression Signature For Anaplastic Wilms Tumormentioning
confidence: 99%
“…We also identified several genes implicated in apoptosis, such as the Huntington disease gene Huntingtin, the double-strand DNA break repair gene hRAD54 (expressed higher in anaplastic tumors than in FH tumors), gamma-interferon-inducible gene IFI16 and caspase-10 (expressed lower in anaplastic tumors than in FH tumors). Wild-type Huntingtin has been shown to be antiapoptotic by inhibiting the conversion of procaspase-9 into active caspase-9 (Rigamonti et al, 2000). Huntingtin also regulates the transcription of BDNF (Zuccato et al, 2001).…”
Section: An Expression Signature For Anaplastic Wilms Tumormentioning
confidence: 99%
“…39(1), [38][39][40][41][42][43][44][45][46] 2007 toxic to neurons and is related to cellular toxicity (Davies et al, 1997;DiFiglia et al, 1997; Cooper et al., 1998;Zala et al, 2005;Benchoua et al, 2006). The activations of caspase-3 or calpain cleaves huntingtin to produce 60-80 kDa sized N-terminal fragments (Jaattela et al, 1998;Wellington et al, 1998;Rigamonti et al, 2000;Kim et al, 2003). Experiments performed in cloned striatal cells have shown that z-VAD-FMK, a broad-spectrum caspase inhibitor, blocks the cleavage of the N-terminal product and increases cell survival (Kim et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, normal huntingtin is antiapoptotic in brain cells (1,2,5,31) and is also found to protect from toxicity induced by the mutant protein (3,4) and to support the production of cortically derived BDNF (10).…”
Section: Proteolysis Of Huntingtin In Primary Neuronsmentioning
confidence: 99%
“…Huntingtin is a 348-kDa cytoplasmic protein that is important for cell survival (1)(2)(3)(4)(5). Interest in this protein stems from the fact that mutation into the encoding gene causes HD, a slowly progressing neurodegenerative disease characterized by the selective death of the striatal and cortical neurons (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation